On extension of pairwise θ-continuous maps - S. K. Sen; M. N. Mukherjee (International Journal of Mathematics and Mathematical Sciences)
The aim of the paper is to find suitable conditions so as to ultimately establish the existence and uniqueness of the extension of a pairwise θ-continuous map onto an arbitrary extension-space of a bitopological space.